Forecast Accuracy and Consistent Preferences for the Timing of Information Arrival - Hofmann, Christian; Rothenberg, Naomi R. (Contemporary Accounting Research, 2019)
ABSTRACT We study a principal's choice of whether to produce an imperfect forecast about a firm's outcome either before or after an agent's effort choice. The early forecast affects the agent's effort choice, which means the forecast can also be used to infer information about the effect of the agent's effort on outcome. The late forecast is more accurate because, by working hard, the agent also learns about productivity, implying that the late forecast has an additional performance measurement role. With verifiable information, the principal prefers a late forecast when the agent's effect on the accuracy of the forecast is either large or small. The agent has consistent preferences when the agent's effect on the accuracy of the late forecast is not too large. With unverifiable information, the agent's information rents imply that the principal cannot use either forecast as a performance measure. Thus, the accuracy of the late forecast has no effect on the principal's preference. However, if the accuracy of the early forecast is low and its decision‐making function is diminished, the principal prefers a late signal.